Analisis Faktor-Faktor yang Menarik Minat Wisatawan Terhadap Keputusan Pemilihan Rumah Makan di Sumatera Selatan - Mustika Permatasari; Abdu Rahman; Zulkifli Harahap; Rahmat Mandasini (Politeknik Pariwisata Makassar, 2020)
As one of the provinces that widely in culinary diversity, South Sumatera is start to be one of tourism destination. This research was conducted in South Sumatera and selected by purposive sampling. The population in this study is tourists visiting South Sumatera. Analysis of the data used is descriptive statistics and parametric inferential statistics for hypothesis testing using Multiple Linear Regression through a SPSS 22 computer program. Based on the t test results obtained smaller t value t table (-4,811 <1,985), this shows that the price variable food (X1) does not significantly influence the level of selection (Y) of Restaurants in South Sumatra. Based on the t test results obtained by t count greater t table (3.570> 1.985), this shows that the service quality variable (X2) has a significant effect on purchase decision (Y) of Restaurants in South Sumatra. Based on the t test results obtained t value is smaller than t table (3,464 <1,985), this shows that the accessibility variable (X3) has a significant effect on the level of selection (Y) of Restaurants in South Sumatra. Based on the t test results obtained by t count greater t table (6.766> 1.985), this shows that the food quality variable (X4) has a significant effect on purchase decision (Y) of Restaurants in South Sumatra.